Extradural Characteristics of the Origins of Lumbosacral Nerve Roots - Haviarova, Zora; Matejcik, Viktor; Kuruc, Roman; Líška, Ján; Steno, Juraj (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2019)
Background and Study Aims A great number of unsuccessful intervertebral herniated disk surgeries in the lumbosacral region have highlighted the importance of a comprehensive knowledge of the different types of nerve root anomalies. That knowledge gained by anatomical studies (and intraoperative findings) might contribute to better results. In our study we focused on intraspinal extradural lumbosacral nerve root anomalies and their possible role in radiculopathy.Material and Methods The study was performed on 43 cadavers within 24 hours after death (32 men and 11 women). Bodies were dissected in the prone position, and a laminectomy exposed the entire spinal canal for the bilateral examination of each spinal nerve root from its origin to its exit through the intervertebral foramen or sacral hiatus. Uncommon extradural features in the lumbosacral region were pursued and documented. The spinal dural sac was also opened, aimed at recognizing the normotyped, prefixed, or postfixed type of plexus.Results A total of 20.93% of anomalies of extradural lumbosacral nerve root origins were observed, with the normotyped plexus prevailing. We observed atypical spacing of exits of lumbosacral roots (four cases), two roots leaving one intervertebral foramen (one case), extradural anastomoses (two cases), and missing extradural nerve root courses (two cases). The results were differentiated according to the normotyped, prefixed, or postfixed plexus type.Conclusion Results of similar studies dealing with anomalies of lumbosacral nerve roots were aimed at improving the results of herniated disk surgeries because ∼ 10% of misdiagnoses are related to ignorance of anatomical variability. Our observations may help explain the differences between the clinical picture and generally accepted anatomical standards.
Keywords: spinal nerve root; lumbosacral; extradural course